Desempenho de materiais cimentícios produzidos com polietilenoglicol e resíduo de catalisador da indústria de petróleo - Tiago Luiz da Costa (2022)
The demand for Portland cement in the civil construction market makes it the most consumed industrialized material in the world, with an annual global production of around 4.0 billion t, projecting an increase of 4.5% per year. Among the production processes of the cement industry, the high levels of pollution consist of limestone extraction, transport of particulate material and in the clinkerization furnace where a large volume of gases is generated. In this scenario, the objective of this work is to investigate the use of low-cost, easily obtainable, unconventional materials, using innovative technologies in the manufacture of concrete, with the proposal of improving performance, durability, reduction of environmental impact and the possibility of preserving the natural resources. Therefore, in the search for sustainability and for alternative materials to be used in the production of concrete, the use of petroleum catalyst residue as a partial substitute for cement was investigated. The petroleum catalyst residue (FCC) used in the study is a thin, mesoporous material, light gray in color, with high specific surface area and high pore volume, consisting essentially of sílica (SiO2) and alumina (Al2O3), and presents satisfactory properties as a pozzolanic material of high reactivity and source of aluminosílicate, which show a high potential of use in the production of concrete. The addition of polyethylene glycol (PEG 400) was also studied, since its properties contribute to greater water retention, favoring the curing of the concrete. Specimens were produced with different dosages, the first with conventional concrete and the others with PEG 400 (1.5%) and substitutions of 2%, 5%, 10% and 20% of catalyst residue, in relation to the total mass of the cement. The specimens were immersed in an aqueous solution of calcium hydroxide and hydrochloric acid (HCl). The effects of polymer additions and residue were investigated in terms of physical, mechanical, durability and morphological properties of the developed concrete. Experiments were carried out to determine the water absorption by capillarity and by immersion, the void and specific masses, the pozzolanicity index of the residue, as well as mechanical characterization tests. The results indicate that the sample with PEG 400 showed a greater consistency in the fresh state (130 mm) than the others (120 mm) and the higher the percentage of FCC, the higher the water absorption rates and the void index and the lower the capillary absorption. The mechanical strength of the sample containing 2% RC and 1.5% PEG 400 obtained a higher average compressive strength (15.67 MPa) than the conventional sample (12.80 MPa). In samples immersed in HCl solution, the higher the FCC content, the greater the decrease in mechanical strength; images obtained through SEM, found that samples containing 2% of FCC addition are less porous than the conventional sample. The development of concrete with innovative materials can help to reduce the negative environmental impacts of the cement industry and also improve product properties.